2019
DOI: 10.1016/j.ebiom.2019.01.051
|View full text |Cite
|
Sign up to set email alerts
|

A GBM-like V-ATPase signature directs cell-cell tumor signaling and reprogramming via large oncosomes

Abstract: Background The V-ATPase proton pump controls acidification of intra and extra-cellular milieu in both physiological and pathological conditions. We previously showed that some V-ATPase subunits are enriched in glioma stem cells and in patients with poor survival. In this study, we investigated how expression of a GBM-like V-ATPase pump influences the non-neoplastic brain microenvironment. Methods Large oncosome (LO) vesicles were isolated from primary glioblastoma (GBM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Practically, most studies are focused on EVs that measure 1 ”m or less, corresponding mostly to exosomes. To date, few articles are based on microvesicles larger than 1 ”m like large oncosome (16)(17)(18)(19). In 2014, The International Society for Extracellular Vesicles (ISEV) proposed Minimal Information for Studies of Extracellular Vesicles ("MISEV") guidelines for EV isolation and purification.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, most studies are focused on EVs that measure 1 ”m or less, corresponding mostly to exosomes. To date, few articles are based on microvesicles larger than 1 ”m like large oncosome (16)(17)(18)(19). In 2014, The International Society for Extracellular Vesicles (ISEV) proposed Minimal Information for Studies of Extracellular Vesicles ("MISEV") guidelines for EV isolation and purification.…”
Section: Introductionmentioning
confidence: 99%
“…Among these nanovesicles, atypically large extracellular vesicles (0.5-5 ”m in diameter) referred to as large oncosomes (LOs) have been identified. LOs can be byproducts of non-apoptotic cells when a large portion of the cellular membrane is shedding from the outward membrane during blebbing events [83]. The shedding process is induced by silencing of the cytoskeletal regulator DIAPH3 (Diaphanous-related formin-3) protein, by the overexpression of oncoproteins (Cav-1 (caveolin-1), HB-EGF (heparin-binding epidermal growth factor), MyrAkt1 (myristoylated Akt1)), or activation of the EGFR and AKT1 pathways [24,[84][85][86][87].…”
Section: Large Oncosomesmentioning
confidence: 99%
“…Terrasi and coworkers suggested that V-ATPase subunits signature that accompanies glioma of different grade may be an independent prognostic marker of IDH wild-type low-grade glioma [ 46 ]. V1G1 subunit of V-ATPase is in many cases overexpressed in glioblastoma cells and is associated with shorter patient survival, moreover in peripheral blood of patients with glioblastoma were detected large oncosomes, a type of extracellular vesicle, that highly express V-ATPase.…”
Section: Lysosomes V-atpases and Cancermentioning
confidence: 99%
“…V1G1 subunit of V-ATPase is in many cases overexpressed in glioblastoma cells and is associated with shorter patient survival, moreover in peripheral blood of patients with glioblastoma were detected large oncosomes, a type of extracellular vesicle, that highly express V-ATPase. Authors supposed that those oncosomes could be useful as liquid biopsy [ 46 ]. Recent in silico study shows, that expression pattern of V-ATPase (combinations in up- and downregulation in the expression ratios of V-ATPase subunits and isoforms) is distinct in different cancers (leukemia, lymphoma, melanoma, myeloma, sarcoma, bladder, brain, breast, cervical, colorectal, esophageal, gastric, head and neck, kidney, liver, lung, ovarian, pancreatic, and prostate cancer) [ 47 ].…”
Section: Lysosomes V-atpases and Cancermentioning
confidence: 99%